Non-Conventional Axonal Organelles Control trpm8 Ion Channel Trafficking and Peripheral Cold Sensing - Madrid-Montecinos, R; Pertusa-Pastor, M (Elsevier B.V., 2020)
TRPM8 is the main ion channel responsible for cold transduction in the somatosensory system. Nerve terminal availability of TRPM8 determines cold sensitivity, but how axonal secretory organelles control channel delivery remains poorly understood. Here we examine the distribution of TRPM8 and trafficking organelles in cold-sensitive peripheral axons and disrupt trafficking by targeting the ARF-GEF GBF1 pharmacologically or the small GTPase RAB6 by optogenetics. In axons of the sciatic nerve, inhibition of GBF1 interrupts TRPM8 trafficking and increases association with the trans-Golgi network, LAMP1, and Golgi satellites, which distribute profusely along the axonal shaft. Accordingly, both TRPM8-dependent ongoing activity and cold-evoked responses reversibly decline upon GBF1 inhibition in nerve endings of corneal cold thermoreceptors. Inhibition of RAB6, which also associates to Golgi satellites, decreases cold-induced responses in vivo. Our results support a non-conventional axonal trafficking mechanism controlling the availability of TRPM8 in axons and cold sensitivity in the peripheral nervous system. Cornejo et al. investigate trafficking of cold-sensitive TRPM8 ion channels in peripheral nerves. A non-conventional secretory machinery comprising Golgi satellites, the trans-Golgi network, and exocytic vesicles is abundant along primary somatosensory axons and terminals. Inhibition of GBF1 and RAB6 modifies these local secretory organelles, impairing TRPM8-dependent cold sensitivity in mice. © 2020